Strategi Sumber Daya Manusia di Masa Pandemi dan New Normal Melalui Remote Working, Employee Productivity, Dan Upskilling For Digital - Raniasari Bimanti Esthi (Forum Kerjasama Pendidikan Tinggi, 2020)
The world is now busy with the Covid-19 pandemic, which has not yet been found in the vaccine, including Indonesia. The purpose of this research is to study the strategies carried out by leaders in the Covid-19 pandemic and new normal. This type of research is a qualitative study by conducting observations, interviews, and literacy studies. The results of this study are leaders in implementing the Covid-19 pandemic and new normal, doing 3 things, namely remote working, employee productivity, and upskills for digital